Sedentary Lifestyle: Overview of Updated Evidence of Potential Health Risks - Park, Jung Ha (Korean J Fam Med, 2020)
One-third of the global population aged 15 years and older engages in insufficient physical activities, which affects health. However, the health risks posed by sedentary behaviors are not well known. The mean daily duration of sedentary behavior is 8.3 hours among the Korean population and 7.7 hours among the American adult population. Sedentary lifestyles are spreading worldwide because of a lack of available spaces for exercise, increased occupational sedentary behaviors such as office work, and the increased penetration of television and video devices. Consequently, the associated health problems are on the rise. A sedentary lifestyle affects the human body through various mechanisms. Sedentary behaviors reduce lipoprotein lipase activity, muscle glucose, protein transporter activities, impair lipid metabolism, and diminish carbohydrate metabolism. Furthermore, it decreases cardiac output and systemic blood flow while activating the sympathetic nervous system, ultimately reducing insulin sensitivity and vascular function. It also alters the insulin-like growth factor axis and the circulation levels of sex hormones, which elevates the incidence of hormone-related cancers. Increased sedentary time impairs the gravitostat, the body’s weight homeostat, and weight gain, adiposity, and elevated chronic inflammation caused by sedentary behavior are risk factors for cancer. Sedentary behaviors have wide-ranging adverse impacts on the human body including increased all-cause mortality, cardiovascular disease mortality, cancer risk, and risks of metabolic disorders such as diabetes mellitus, hypertension, and dyslipidemia; musculoskeletal disorders such as arthralgia and osteoporosis; depression; and, cognitive impairment. Therefore, reducing sedentary behaviors and increasing physical activity are both important to promote public health.